2011
DOI: 10.1111/j.1365-2036.2010.04572.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis in a large sample of patients with coeliac disease - a nationwide cohort study

Abstract: SUMMARY BackgroundResearch suggests a positive association between coeliac disease and tuberculosis (TB), but that research has often been limited to in-patients and small sample size. We examined the relationship between TB and coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…In contrast with some older studies on comorbidities in CD[14], we did not rely on inpatient data to identify our exposure variable (CD). This is important since inpatient care is not routine for the diagnosis of CD, and our earlier research has shown that complications are more frequent in individuals hospitalized with their CD than in those identified through biopsy record data (for instance the HR for tuberculosis was 3.7 in inpatients with CD[37] compared with 2.0 in CD patients identified through biopsy records[38]). We used biopsy reports from all of Sweden's pathology departments to identify CD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with some older studies on comorbidities in CD[14], we did not rely on inpatient data to identify our exposure variable (CD). This is important since inpatient care is not routine for the diagnosis of CD, and our earlier research has shown that complications are more frequent in individuals hospitalized with their CD than in those identified through biopsy record data (for instance the HR for tuberculosis was 3.7 in inpatients with CD[37] compared with 2.0 in CD patients identified through biopsy records[38]). We used biopsy reports from all of Sweden's pathology departments to identify CD.…”
Section: Discussionmentioning
confidence: 99%
“…In both these series, with strong associations between CD and intussusception, participants were recruited from single tertiary centers, making it is possible that this procedure selected cases with more severe CD and intussusception [11,13], or that these patients were at higher risk of undergoing investigation or contacting health care for a number of disorders. We have previously shown that the relative risk of another disorder in CD (tuberculosis) is twice as high in CD patients identified through hospital records [26] as in patients identified through biopsy reports [27]. Further, the risk of mortality in CD seems higher in patients with a hospital record of CD [28] than in patients diagnosed through biopsy reports [19].…”
Section: Discussionmentioning
confidence: 99%
“…Swedish nationwide population-based cohort studies involving more than 28 000 coeliac disease cases with a median follow-up of 9 years have found that coeliac disease is associated with an increased risk of hospital admission for influenza (hazard ratio 2.1) [73], developing tuberculosis (hazard ratio 2.0) [74], lymphoproliferative malignancy (hazard ratio 2.82) [75], cataracts (hazard ratio 1.28) [76], psoriasis (hazard ratio 1.72) [77], asthma (hazard ratio 1.6) [78], atrial fibrillation (hazard ratio 1.34) [79], suicide (hazard ratio 1.55) [80], ESRD (hazard ratio 2.87) [81 && ] and a negligible risk of future stroke (hazard ratio 1.10) [82]. Most notably, the three-fold increased risk of future ESRD was irrespective of age at coeliac disease diagnosis [81 && ], prompting the need to monitor renal function in coeliac disease patients.…”
Section: Mortality and Morbidity Riskmentioning
confidence: 99%